2010
DOI: 10.1021/ml1001085
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Orally Bioavailable, Potent, and Selective Inhibitor of GlyT1

Abstract: Amalgamation of the structure-activity relationship of two series of GlyT1 inhibitors developed at Merck led to the discovery of a clinical candidate, compound 16 (DCCCyB), which demonstrated excellent in vivo occupancy of GlyT1 transporters in rhesus monkey as determined by displacement of a PET tracer ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…130 Therefore, GlyT1 inhibitors would be predicted to control synaptic glycine concentrations and to potentiate NMDA receptor function in vivo to ameliorate the negative symptoms of schizophrenia. 131 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 35 moiety yielded 99 (DCCCyB), 132 with a marginal increase in potency. However, this molecular modification significantly improved human and rat liver microsomal turnover compared to 98 as shown in Figure 43.…”
Section: Compounds 91 (Naltrexone/vivitrol) and 92 (Nalmefene/revex):mentioning
confidence: 99%
See 1 more Smart Citation
“…130 Therefore, GlyT1 inhibitors would be predicted to control synaptic glycine concentrations and to potentiate NMDA receptor function in vivo to ameliorate the negative symptoms of schizophrenia. 131 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 35 moiety yielded 99 (DCCCyB), 132 with a marginal increase in potency. However, this molecular modification significantly improved human and rat liver microsomal turnover compared to 98 as shown in Figure 43.…”
Section: Compounds 91 (Naltrexone/vivitrol) and 92 (Nalmefene/revex):mentioning
confidence: 99%
“…However, this molecular modification significantly improved human and rat liver microsomal turnover compared to 98 as shown in Figure 43. 132 Compound 99 has a good PK profile in animal models. Furthermore, it is not a substrate of P-gp, and thus achieves a high brain to plasma ratio of 2.3, and is efficacious in various rodent models.…”
Section: Compounds 91 (Naltrexone/vivitrol) and 92 (Nalmefene/revex):mentioning
confidence: 99%
“…Merck's effort began with an HTS effort that identified 21 [23], which evolved into related congeners 22-24 [24][25][26] and ultimately the clinical candidate 25, MK-2637 (Figure 16.7) [51]. Here, we employed the same scaffold hopping strategies described previously, and were rapidly able to develop four patented series of GlyT1 inhibitors, represented by 26-28 (Figure 16.8) [15][16][17][18][19][20].…”
Section: Scaffold Hopping To Access Novel Glycine Transporter Type 1 mentioning
confidence: 99%
“…All four cases withstood patent examination, and the US patents are beginning to issue [15,16]. Similar to the T-type calcium antagonists described earlier, these series displayed enantiospecific activity [15][16][17][18][19][20] and provided rapid access to potent GlyT1 inhibitors with comparable potency (IC 50 values from 750 pM to 300 nM), selectivity, DMPK profiles, and pharmacodynamics profiles to those developed by Merck [23][24][25][26]51]. Clear themes emerged as bioisosteric replacements for the piperidine core, and solid IP resulted once again.…”
Section: Scaffold Hopping To Access Novel Glycine Transporter Type 1 mentioning
confidence: 99%
“…1), which has been reported as a potential GlyT1 inhibitor in the development of anti-schizophrenia drugs and which exhibits excellent pharmacokinetic properties (Oral bioavailability 38%, t 1/2 : 11.8 h), [22][23][24] was evaluated for GlyT1 inhibition and anti-seizure activity in a mouse model. Our results showed that M22 elevated the seizure threshold in the MEST test and did not impair locomotion or motor coordination in mice.…”
mentioning
confidence: 99%